Chronic natural arsenic exposure affecting histoarchitecture of gonads in Black Bengal goats (Capra aegagrushircus) - Wares, Md. Abdul; Awal, Md. Abdul; Das, Shonkor Kumar; Hannan, Md. Abdul; Anas, Md. Abu; Latif, Md. Abdul; Masud, Neshat (Journal of Advanced Veterinary and Animal Research, 2015)
Arsenic is a major water pollutant that may cause serious health hazard (e.g., infertility) in human and animal. We evaluated the changes in histoarchitecture of testes and ovaries of adult Black Bengal goats (n=10) reared in arsenic affected areas in Bangladesh. Grossly, we found insignificant variations among the testes and ovaries, but histological evaluation revealed an extensive alteration in morphology of both testes and ovaries in the arsenic affected goats. In testes, the thickening of tunica albugenia and trabeculae, widening of intertubular space between seminiferous tubules, and narrowing in diameter of seminiferous tubules were observed. In ovaries of arsenic affected goats, significant decrease in number of primary follicles and antral follicles were observed. The diameters of secondary and antral follicles were significantly reduced. The granulosa layer of antral follicles showed marked thickening. The findings indicate that chronic arsenic exposure alters the histoarchitecture of both male and female gonads in Black Bengal goat, and thereby may affect their reproductive performance. http://dx.doi.org/10.5455/javar.2015.b61